The relationship between transformational leadership and overall school effectiveness in primary schools, Selangor, Malaysia based on teachers perception - Talebloo, Baharak; Basri, Ramli; Hassan, Aminuddin; Asimiran, Soaib (Human Resource Management Academic Research Society, 2017)
The current study is an attempt to explore the relationship between transformational leadership and overall school effectiveness in primary schools, Selangor, Malaysia based on teachers? perception. This study utilized stratified random sampling method by choosing 72 primary schools and 490 teachers with the response rate of (n=410) in 6 districts of Selangor state (Gombak, Hulu Langat, Hulu Selangor, Klang, Kuala Langat and Kuala Selangor) and from three types of National, National type Chinese and National type Tamil school based on their urban and rural locations. Data analysis conducted by using descriptive statistic and Pearson product moment correlation. The results indicate that there were positive, significant, and small to moderate relationships were found between five organizational citizenship behaviour dimensions and overall school effectiveness. This study proposed several recommendations to the Ministry of Education, headmasters, teachers, and school administrators, to improve the level of school effectiveness by practicing transformational leadership dimensions especially “building shared vision” and “models behaviour” dimension. Moreover, they can develop, maintain, and elevate the level of school effectiveness by exhibiting civic virtue, altruism, and conscientiousness behaviours as the dimensions of organizational citizenship behaviour in primary schools in Selangor, Malaysia.